Analyzing the effect of waste jarosite as an alternative filler on the engineering properties of asphalt mixes - Islam S.S.; Ransinchung G.D.R.N.; Choudhary J. (My University, 2025)
Zinc extraction engenders massive production of non-biodegradable Jarosite (JS) as an industrial waste that faces difficulty concerning its disposal. This study presents a novel approach to utilize JS as a filler in asphalt mixes. The asphalt mixes containing JS was designed as per Marshall mix design, and their engineering properties were compared with the mixes containing two conventional fillers (stone dust (SD) and hydrated lime (HL)) and one widely used waste filler (coal fly ash (FA)) at same mass proportion. The performance of asphalt mixes was compared using methods like indirect tensile strength test, four-point beam bending test, wheel rut test, Cantabro test, resilient modulus and modified Lottman tests. The use of JS in place of conventional SD improved the Marshall stability, indirect tensile strength, and rutting resistance of the asphalt mixes by 17, 25, and 27% respectively. This was majorly attributed to the high porosity, finer nature, higher specific surface area and high asphalt-filler interaction of JS. The moisture resistance of JS mixes was also found to be 3.5 and 10% better than FA and SD mixes respectively. Although, JS mixes showed relatively lower fatigue life than other mixes due to their high stiffness; however, fatigue life was found to be comparable with conventional HL mixes tested at lower strain levels. The overall conclusions of this study ascertain the utility of JS as an alternative filler and also paved its way for its safe disposal. © 2020 Elsevier Ltd